2019
DOI: 10.1002/jcp.28365
|View full text |Cite
|
Sign up to set email alerts
|

Potential candidate biomarkers associated with osteoarthritis: Evidence from a comprehensive network and pathway analysis

Abstract: Osteoarthritis (OA) is one of the most common forms of arthritis world widely. Some key genes and diagnostic markers have been reported due to the development of modern molecular biology technologies. However, the etiology and pathogenesis of OA remains unknown. In this study, an integrated network and pathway analysis towards the biological function of OA‐associated genes was conducted to provide valuable information to further explore the etiology and pathogenesis of OA. A total of 2,548 genes which reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The targets having degrees higher than the average value were defined as the key targets. Furthermore, to identify the core local sub-networks ( clusters ) with the high clustering scores, we conducted Molecular Complex Detection (MCODE) cluster analysis of candidate targets using the Cytoscape plugin MCODE clustering algorithm (node score cut-off value = 0.2, degree cut-off value = 2, K-core = 2, MAX depth value = 100) ( Zhang et al, 2019 ; Ahmed, 2020 ). The higher the clustering scores were, the more important the MOCDE sub-networks were in the regulatory network of DPTS-induced liver injury.…”
Section: Methodsmentioning
confidence: 99%
“…The targets having degrees higher than the average value were defined as the key targets. Furthermore, to identify the core local sub-networks ( clusters ) with the high clustering scores, we conducted Molecular Complex Detection (MCODE) cluster analysis of candidate targets using the Cytoscape plugin MCODE clustering algorithm (node score cut-off value = 0.2, degree cut-off value = 2, K-core = 2, MAX depth value = 100) ( Zhang et al, 2019 ; Ahmed, 2020 ). The higher the clustering scores were, the more important the MOCDE sub-networks were in the regulatory network of DPTS-induced liver injury.…”
Section: Methodsmentioning
confidence: 99%
“…In search of both predictive and descriptive OA biomarkers, other cartilage ECM components were identified in bioinformatic approaches. Co-expression network and pathway analysis of gene expression profiles from different OA datasets were performed [ 74 , 75 ]. The expression profile of genes clearly associated with OA (like e.g., MMP2, COL6A1, COL9A1-3) and the synthesis and degradation of the encoded proteins has to be evaluated in future studies.…”
Section: The Role Of Proteases and Cytokines In Oamentioning
confidence: 99%
“…The development of next-generation technologies such as largescale sequencing and multianalyte assay has recently facilitated the discovery of a slew of potential biomarkers for OA (Cong et al, 2017;Xu et al, 2019;Zhang et al, 2019;Hong et al, 2020). For example, Li et al (2017), identified several differentially expressed genes, including a disintegrin and metalloproteinase 8 (Adam8), arginase 1 (Arg1) and microRNAs (miRNAs) such as miRNA-200b, which might play key roles in the pathogenesis of mice OA based on microarray analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, functional disruption of collagen in cartilage has been shown to be a very important contributing factor to OA. Quantitative detection of collagen synthesis may facilitate early identification and prediction of OA (Zhang et al, 2019). However, none of these biomarkers is specific, which makes diagnosis and treatment of OA still a challenge.…”
Section: Introductionmentioning
confidence: 99%